115 Play in the children's hospital; discreet activity or way of life?. (December 2018) - Walsh, L
Abstract : This paper examines the therapeutic potential of promoting play as an 'ethos' or way of being as opposed to an activity carried out in discreet locations within a hospital environment. In a specialist children's hospital, the children attending have the most complex conditions and it is posited here that in a system which pathologises children due to physical illnesses, that Play and the fundamental importance of it may be lost to the dominant pathological narrative. Staff perceptions of play and the value of it should be interrogated therefore to uncover assumptions and to ensure that rich environments can be created to offer the best conditions in which play can happen. Great Ormond Street Hospital is the leading children's hospital in the UK and play is a fundamental part of every-day life. It is acknowledged that play in its many forms enhances whole child (cognitive creative, emotional, physical, social) development (Patte, 2015), yet there is still a lack of clarity around what play is and its potential value. This paper analyses events around an outbreak of an infectious illness within the hospital. Different interpretations and understanding of infection control directives led to the most extreme interpretations of the rules being enforced and play spaces co-created by children and staff were cleared and materials destroyed. This led to an unpicking of the assumptions and value positions held by actors in the incident. Using theories of place relationship, affordances (Kytta), Production of Space (Lefebvre) as well as notions of social and cultural determination, the narrative is presented using lively, playful story-telling methods appropriate to play theory, interweaving stories from staff and children with theory.